Implementation Of the National Movement Program To Increase The Production And Quality Of Cocoa Plants In Sigi District: Study On the Performance Of Food Crop Service Extension Officers, Horticulture And Plantations of Sigi Regency - Irwan Waris; Alam Anshary (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aims to determine and understand the performance of plantation field extension workers who work in the context of managing the National movement program of cocoa in Sigi Regency. This research uses the performance theory proposed by Robbins, consisting of 3 main aspects of assessment, namely: motivation, ability, and opportunity. The research method used, qualitative with a descriptive approach, involved a number of informants interviewed during the study, in addition to displaying as supporting data secondary, the results of the study of literature and the study of documents. This study concluded that the performance of agricultural extension workers working in the National movement program for cocoa in Sigi Regency has not been maximized, not only due to aspects of: motivation, ability, and opportunity, but also caused by various other factors.